The effect of total-ABL, GUS and B2M control genes on BCR-ABL monitoring by real-time RT-PCR - Rulcová, Jana; Zmeková, Václava; Zemanová, Zuzana; Klamová, Hana; Moravcová, Jana (Leukemia research, 2007)
We compared the effect of control genes (CG): total Abelson (total-ABL), beta-2-microglobulin (B2M) and beta-glucuronidase (GUS), recommended in the Europe Against Cancer (EAC) program, on real-time BCR-ABL monitoring in patients with chronic myeloid leukemia (CML). We focused on the stability of CG expressions during therapy and the effect of the CGs on BCR-ABL ability to characterize the disease status and disease prognosis, issues that have not been addressed yet. The results showed B2M as a very convenient CG for BCR-ABL monitoring. On the contrary, the widely used total-ABL was not confirmed as appropriate for normalization of gene expression in CML.
Keywords: Male; chronická myeloidní leukemie; lidé středního věku; beta 2-Microglobulin; Glucuronidase; Humans; Middle Aged; senioři; Leukemia, Myelogenous, Chronic, BCR-ABL Positive; mužské pohlaví; glukuronidasa; Female; Aged; komplementární DNA; ženské pohlaví; RNA nádorová; RNA, Messenger; protoonkogenní proteiny c-abl; Adult; DNA, Complementary; beta-2-mikroglobulin; regulace genové exprese u leukemie; RNA, Neoplasm; bcr-abl fúzní proteiny; Fusion Proteins, bcr-abl; polymerázová řetězová reakce s reverzní transkripcí; dospělí; lidé; Proto-Oncogene Proteins c-abl; Reverse Transcriptase Polymerase Chain Reaction; Gene Expression Regulation, Leukemic; messenger RNA